Differential expression of microRNAs in Alzheimer's disease brain, blood, and cerebrospinal fluid. Issue 11 (5th September 2019) - Takousis, Petros; Sadlon, Angélique; Schulz, Jessica; Wohlers, Inken; Dobricic, Valerija; Middleton, Lefkos; Lill, Christina M.; Perneczky, Robert; Bertram, Lars
Abstract: Introduction: Several microRNAs (miRNAs) have been implicated in Alzheimer's disease pathogenesis, but the evidence from individual case‐control studies remains inconclusive. Methods: A systematic literature review was performed, followed by standardized multistage data extraction, quality control, and meta‐analyses on eligible data for brain, blood, and cerebrospinal fluid specimens. Results were compared with miRNAs reported in the abstracts of eligible studies or recent qualitative reviews to assess novelty. Results: Data from 147 independent data sets across 107 publications were quantitatively assessed in 461 meta‐analyses. Twenty‐five, five, and 32 miRNAs showed studywide significant differential expression (α < 1·08 × 10 −4 ) in brain, cerebrospinal fluid, and blood‐derived specimens, respectively, with 5 miRNAs showing differential expression in both brain and blood. Of these 57 miRNAs, 13 had not been reported in the abstracts of previous original or review articles. Discussion: Our systematic assessment of differential miRNA expression is the first of its kind in Alzheimer's disease and highlights several miRNAs of potential relevance.